Peran Intelijen Maritim Terhadap Keamanan Laut di Selat Sunda - Hartawan, Mohammad Zaki; Pramono, Agung; Yudho, Fafan (Rekayasa, 2021)
The Sunda Strait is one of the shipping lanes that is part of ALKI I which is traversed by cargo ships, tankers, tugboats, fishing vessels and military ships as well as ships using the Sunda Strait to pass from the Indian Ocean to the Java Sea or continue to the Pacific Ocean or vice versa. The tasks and roles of maritime intelligence are an integral part of the overall intelligence activities and operations of the Indonesian Navy, and have a role in providing input and advice on the development of weather conditions, terrain and enemy/future enemies as well as maritime aspects to the leadership in determining policies and decisions on operational aspects. and other interests through a series of activities (functions) of investigation, security and fundraising. The method used in this research is quantitative with a questionnaire using a Likert scale and distributed to 60 people who serve in the ranks of Lantamal III which is then analyzed using Linear Regression Analysis. From the results of the analysis obtained a regression model Y = 4.621 + 0.901 X and it is known that Maritime Intelligence has an influence on Marine Security in the Sunda Strait that is equal to 89,51 %.